Exploring Pediococcus sp. M21F004 for Biocontrol of Bacterial and Fungal Phytopathogens - Van Thi Nguyen; Yong Min Kwon; Ae Ran Park; Nan Hee Yu; Grace Choi; Jin-Cheol Kim (Marine Drugs)
This study explores the biocontrol potential of Pediococcus sp. M21F004, a lactic acid bacteria (LAB) isolated from marine environments, against several bacterial and fungal phytopathogens. Out of 50 marine bacterial isolates, Pediococcus sp. M21F004 was selected for its exceptional antimicrobial activity. The strain, isolated from the intestine of a starry flounder, was identified as Pediococcus sp. Gas chromatography–mass spectrometry (GC-MS) analysis revealed that oleic acid (OA) is a key antimicrobial compound produced by Pediococcus sp. M21F004. In vitro assays showed that the culture broth (CB) of Pediococcus sp. M21F004, as well as OA, exhibited significant inhibitory effects against pathogens such as Fusarium oxysporum, Clarireedia homoeocarpa, and Pectobacterium carotovorum subsp. carotovorum. In vivo tests on cucumber Fusarium wilt, creeping bentgrass dollar spot, tomato bacterial wilt, and kimchi cabbage soft rot further demonstrated the strain’s efficacy in reducing disease severity. Moreover, OA had the highest control value of 74% against tomato bacterial wilt, followed by 64.1% against cucumber fusarium wilt, 42.5% against kimchi cabbage soft rot, and 16.5% against creeping bentgrass dollar spot. These findings suggest that Pediococcus sp. M21F004 and its metabolite OA offer promising alternatives to chemical pesticides, contributing to sustainable plant disease management by promoting resistance induction and providing an eco-friendly approach to agriculture.